2019
DOI: 10.1111/jsbm.12397
|View full text |Cite
|
Sign up to set email alerts
|

Entrepreneurial Leadership, Patriarchy, Gender, and Identity in the Arab World: Lebanon in Focus

Abstract: In this paper, we apply insights from poststructuralist feminist theory to contribute to entrepreneurial leadership. By drawing on 21 individual narratives with Lebanese women entrepreneurs, we explore how they determine their status as entrepreneurial leaders and establish their entrepreneurial identities. Although the factors of gender, sociocultural values, and agency can be counteractive, it is agency that creates space for entrepreneurship for women and provides them a means to navigate structural inequal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
63
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 62 publications
(70 citation statements)
references
References 55 publications
(183 reference statements)
3
63
0
4
Order By: Relevance
“…We adopted an interpretive qualitative methodology, which allows us to build an understanding of the experiences of Muslim women entrepreneurs in Lebanon and to contextualize their experiences in socio-cultural, economic, and religious contexts (Cohen 2006;Tlaiss and Kauser 2018). Given our interest in understanding the role of Islam as experienced and interpreted by the women, we conducted research for and with (rather than about) our respondents (Sprague 2016;McAdam et al 2019a).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…We adopted an interpretive qualitative methodology, which allows us to build an understanding of the experiences of Muslim women entrepreneurs in Lebanon and to contextualize their experiences in socio-cultural, economic, and religious contexts (Cohen 2006;Tlaiss and Kauser 2018). Given our interest in understanding the role of Islam as experienced and interpreted by the women, we conducted research for and with (rather than about) our respondents (Sprague 2016;McAdam et al 2019a).…”
Section: Methodsmentioning
confidence: 99%
“…Lebanon was chosen as our research setting for a number of reasons. First, it is often described as a patriarchal, masculine Arab country with sociocultural values that favour a traditional division of labour and promote strictly defined gender roles (Tlaiss and Kauser 2018). Despite these restrictive social practices and cultural values, Lebanon has the highest female-to-male entrepreneur ratio in early stage entrepreneurship (69%) among the seven Arab countries that participated in the 2017 GEM's report (Al Hussaini and Hill 2018) and the highest gender equality index based on the Arab Barometer data (Kostenko et al 2016).…”
Section: Empirical Settingmentioning
confidence: 99%
See 1 more Smart Citation
“…Sandybayev (2019) conducted a quantitative analysis of 87 small-and medium-sized enterprise (SME) participants in the United Arab Emirates and concluded that the entrepreneurial leadership style had more opportunities to effectively manage the organization than just a manager or just an informal leader without status authority, which might improve the organizational performance of the enterprise. Different entrepreneurial psychological leadership styles may have different effects on the organizational learning ability and organizational performance of enterprises, but a series of influence situations still need to be studied (Tlaiss and Kauser, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…This approach allowed us to explore and understand the challenges and barriers that Native Americans face during their pursuit of actual careers. Like other exploratory studies in the interpretative tradition (Tlaiss & Kauser, 2018), it is important to stress that the primary objective of this study was to gain a deeper understanding of the challenges of Native Americans and to shed light on their struggles, not to generalize or make predictions based on the findings in this study. According to Max Weber (cited in Crotty, 1998, p. 67), an early theorist of this framework, interpretivism does not seek causality.…”
Section: Methodsmentioning
confidence: 99%